2013
DOI: 10.1186/2045-5380-3-11
|View full text |Cite
|
Sign up to set email alerts
|

D-Cycloserine as an augmentation strategy for cognitive behavioral therapy of anxiety disorders

Abstract: The goal of this review is to examine the clinical studies on d-cycloserine, a partial glutamatergic N-methyl-D-aspartate agonist, as an augmentation strategy for exposure procedures during cognitive behavioral therapy for anxiety disorders. Although cognitive behavioral therapy and anxiolytic medications are more effective than placebo for treating anxiety disorders, there is still considerable room for further improvement. Traditional combination strategies typically yield disappointing results. However, rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
42
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 67 publications
(101 reference statements)
1
42
0
Order By: Relevance
“…It is also possible that D-cycloserine augments learning of not only fear extinction but also fear reconsolidation. 11 Fear learning and reconsolidation within less successful exposure sessions may have been enhanced by D-cycloserine, thereby masking or neutralizing augmented gains made during other more successful E/RP tasks. Indeed, D-cycloserine augmentation after successful exposures has been associated with enhanced therapeutic outcomes, 12,13 while some evidence suggests that D-cycloserine after less successful within-session distress habituation can actually result in fear reconsolidation and attenuated outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also possible that D-cycloserine augments learning of not only fear extinction but also fear reconsolidation. 11 Fear learning and reconsolidation within less successful exposure sessions may have been enhanced by D-cycloserine, thereby masking or neutralizing augmented gains made during other more successful E/RP tasks. Indeed, D-cycloserine augmentation after successful exposures has been associated with enhanced therapeutic outcomes, 12,13 while some evidence suggests that D-cycloserine after less successful within-session distress habituation can actually result in fear reconsolidation and attenuated outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…10 It is hypothesized that acutely dosed D-cycloserine can augment exposure therapy, particularly when the anxiety-provoking trigger has been successfully extinguished. 1113 Initial studies of D-cycloserine augmentation of exposure therapy in anxiety have yielded mixed results, with evidence supporting this approach for acrophobia, 14 social phobia, 15,16 posttraumatic stress, 17 and panic disorder, 18 while others have found limited benefit in treating social phobia, 19 posttraumatic stress, 2022 and panic disorder. 23 …”
mentioning
confidence: 99%
“…A growing body of literature indeed showed that DCS targeting the consolidation of inhibitory memory might improve the long-term efficacy of CBT (see for extensive reviews of the literature, Graham, Callaghan, & Richardson, 2014;Milad, Rosenbaum, & Simon, 2014). Even though DCS emerges as a potential augmentation strategy for CBT, the beneficial effect of DCS depends on successful within-session extinction and is again (like yohimbine) restricted to the context in which extinction is learned (Bouton, Vurbic, & Woods, 2008;Hofmann, Wu, & Boettcher, 2013;Woods & Bouton, 2006). Hence, the discovery of cognitive enhancers (e.g., DCS, yohimbine) may be promising by accelerating treatment effectiveness, but they do not prevent the return of fear since they leave the fear memory intact.…”
Section: A Challenge For the Cognitive Accountmentioning
confidence: 98%
“…Certain similarity of mechanisms acutely induced by DCS or those appearing 24 h after ketamine administration can be postulated based on the above-depicted pro-plastic downstream effects of ketamine. To exploit such potentially useful effects in clinical dimensions, studies on DCS explored this potential for repeated dose schemes, which, however, lead at least in part to failed trials [113]. The reasons for such unsuccessful translation into a repeated dosage protocol necessary for the exploitation of pro-plastic effect along to the therapeutic process are largely unknown.…”
Section: Neurobiological Augmentation Of Psychotherapeutic Learningmentioning
confidence: 99%